Gestión operativa de capacitación “Comercialización de productos” del MAG del cantón de Baba - Cordova Franco, Cynthia Karina (2021)
Ecuador is a country known for the great demand of farmers to continue, in recent times we have observed the lack of support for the productive matrix by the government of the day and institutions aimed at meeting the needs of farmers such as MAG, this institution It was created to help small producers can receive fair payment for their production, to prevent large marketers from making use of buying the crops at a low price, harming the producer and which in turn ensure the country's economy and agricultural production, This price regulating institution constantly visits collection centers to supervise prices and quality so that the commercialization is developed in an equitable way and that the producers have profitability in their harvests. The present objective is to determine the impact caused by the decrease in the commercialization flows of their crops in the Baba canton in order to obtain an income to support their families.